Evaluation of dynamic dermoscopic features of melanoma and benign naevi by sequential digital dermoscopic imaging and total body photography in a high‐risk Australian cohort. (18th January 2023) - Nguyen, Jennifer; Doolan, Brent J; Pan, Yan; Vestergaard, Tine; Paul, Eldho; McLean, Catriona; Haskett, Martin; Kelly, John; Mar, Victoria; Chamberlain, Alexander
Abstract: Background/Objectives: Sequential digital dermoscopic imaging (SDDI) and total body photography (TBP) are recommended as a two‐step surveillance method for individuals at high‐risk of developing cutaneous melanoma. Dermoscopic features specific to melanoma have been well described, however, dynamic changes on serial imaging are less understood. This study aims to identify and compare dermoscopic features in developing melanomas and benign naevi that underwent SDDI and TBP to understand which dermoscopic features may be associated with a malignant change. Method: Histopathology reports from a private specialist dermatology clinic from January 2007 to December 2019 were reviewed. Histopathologically confirmed melanoma and benign naevi that underwent SDDI and TBP with a minimum follow‐up interval of 3 months were included. Results: Eighty‐nine melanomas (38.2% invasive, median Breslow thickness 0.35 mm, range: 0.2–1.45 mm) and 48 benign naevi were evaluated by three experienced dermatologists for dermoscopic changes. Features most strongly associated with melanoma included the development of neovascularisation, asymmetry and growth in pigment network, additional colours, shiny white structures, regression, structureless areas and change to a multi‐component pattern. The presence of atypical vessels ( p = 0.02) and shiny white structures ( p = 0.02) were significantly associated with invasive melanoma. Conclusion: Evaluation for certain evolving dermoscopic features in melanocytic lesions monitored by SDDI and TBP is efficient in assisting clinical decision making. SDDI with TBP is an effective tool for early detection of melanoma.